2021
DOI: 10.1088/1758-5090/ac41a1
|View full text |Cite
|
Sign up to set email alerts
|

Melt electro-written scaffolds with box-architecture support orthogonally oriented collagen

Abstract: Melt Electro-Writing (MEW) is a state-of-the-art technique that supports fabrication of 3D, precisely controlled and reproducible fiber structures. A standard MEW scaffold design is a box-structure, where a repeat layer of 90° boxes is produced from a single fiber. In 3D form (i.e., multiple layers), this structure has the potential to mimic orthogonal arrangements of collagen, as observed in the corneal stroma. In this study, we determined the response of human primary corneal stromal cells and their depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…F-actin staining demonstrated that the chosen scaffold architectures can tune the cell spatial arrangement, in agreement with previous in vitro studies [28][40] [51][53] [60]. A square-shape pore was responsible for an orthogonally oriented distribution of the cell cytoskeleton [61][62], while the use of diamond-like pores allowed for a preferential cell organisation. The narrower the printed WA the higher the obtained alignment of cell along the major diagonal demonstrating the contact guidance provided by the MEW framework.…”
Section: Discussionsupporting
confidence: 86%
“…F-actin staining demonstrated that the chosen scaffold architectures can tune the cell spatial arrangement, in agreement with previous in vitro studies [28][40] [51][53] [60]. A square-shape pore was responsible for an orthogonally oriented distribution of the cell cytoskeleton [61][62], while the use of diamond-like pores allowed for a preferential cell organisation. The narrower the printed WA the higher the obtained alignment of cell along the major diagonal demonstrating the contact guidance provided by the MEW framework.…”
Section: Discussionsupporting
confidence: 86%
“…Corneal stroma replacement was also suggested to be grown onto melt electrowritten PCL with an orthogonal 3D arrangement, showing deposited collagen fibrils of the corneal stromal cells laid entirely within and across the open pores of the scaffold. This confirmed crucial topographical cues for cell support since collagen was laid only in the uniaxial direction of the aligned fibers in the case of solution electrospun scaffolds [ 23 ]. A structure similar to the native cornea was also successfully fabricated by 3D printing of a composite ink of gelatin methacrylate modified by hyaluronic acid.…”
Section: Introductionmentioning
confidence: 70%
“…Cells cultured on electrospun substrates typically deposit ECM materials over the surface of the electrospun fibers. However, collagen fibrils produced by the cells can be formed between the electrospun fibers because of their relatively high mechanical properties compared with other ECM components, such as GAG (Bosworth et al, 2021; Szewczyk et al, 2018). Thus, SEM imaging at high magnification showed that collagen fibrils were formed in both cell‐cultured constructs between electrospun fibers (Figure 5a,b).…”
Section: Resultsmentioning
confidence: 99%